Single-nucleotide polymorphisms in ialB, gltA and rpoB genes of Bartonella bacilliformis isolated from patients in endemic Peruvian regions. - Yanina Zarate-Sulca; Karen Daphne Calvay-Sanchez; Víctor Jimenez-Vasquez; Joaquim Ruiz; Oscar Acosta-Conchucos; Giovanna Mendoza-Mujica (Public Library of Science (PLoS), 2023)
Bartonella bacilliformis is a Gram-negative, aerobic bacterium and the known causal agent of Carrion's disease, still considered a neglected disease. There is limited information about the nucleotide sequences of this bacterium in international databases, and few studies have addressed the genetic diversity of B. bacilliformis. We analyzed a total of 20 isolates of B. bacilliformis from the Peruvian regions of Ancash and Cajamarca. Three genes (ialB, gltA, and rpoB) were sequenced in each isolate and nucleotide sequences retrieved from GenBank (16 B. bacilliformis genomes) were also included in the study. All this information was merged in order to obtain clearer evidence of the phylogenetic relationships of B. bacilliformis. In the phylogenetic analysis conducted with the concatenated markers, four isolates (B.b-1, B. b-3, B. b- 7, B.b-8) from the Ancash region were observed to form a subgroup different from B. bacilliformis type strain KC583, showing dissimilarity levels of 5.96% (ialB), 3.69% (gltA) and 3.04% (rpoB). Our results suggest that B. bacilliformis consists of two different subgroups. Future investigations are needed to establish the taxonomic status of these subgroups.